The Effect of Adding a Natural Mixture of Essential Oils (Consisting of Basil, Cumin, Bay, Lemon, Thyme, Sage, Tea and Thyme Oils) to the Diet on Productive Performance, Carcass Characteristics and Histological Composition of the Large Intestine in Broile - Ahmed, Ahmed Tareq (American Journal of Biology and Natural Sciences, 2025)
The city of Baghdad, Iraq, with a view to assessing the impact of adding a natural mix of aromatic oils to feed on growth and sacrifice and intestinal health in meat chicken. The mixture includes the essential oils for basil, latency, leaver, lemon, thyme, marmese, and tea. The experience was made on 180 kg of ROS type. Chicken has been divided into several pilot groups as well as an officer group that has not added any aromatic oils. Aromatic oils were added to feeds rates from 20 mg to 70 mg per kilogram of feed. The results indicated that the addition of this mixture of aromatic oils to feed had a positive impact on growth rates, with the highest percentage of aromatic oils compared to the setting set, especially during the stages of fattening and final growth. The Sadr’s weights recorded in two groups, which were added to 10.4% and 7.4%, respectively, compared with the control group. The intestinal analysis showed a notable improvement in the intestinal structure. The second group showed an increase in high gays, third and fourth and sixth groups showed an increase in exhibitors, indicating improvement in the absorption of nutrients.